Effects of age on antibody affinity maturation. (1st April 2003) - Dunn-Walters, D.K.; Banerjee, M.; Mehr, R.
Abstract : The elderly are more susceptible to infectious diseases. Mortality and morbidity from infections increase sharply over the age of 65 years. At the same time, the efficacy of vaccinations in the elderly is decreased. The elderly also have an increased incidence of cancer and inflammatory diseases. All the above indicate an age-related dysregulation of the immune system. Evidence suggests that the change in the humoral immune response with age is a qualitative rather than a quantitative one, i.e. it is the affinity and specificity of the antibody that changes, rather than the quantity of antibody produced. There are a number of possible causes of this failure, one of which is a defect in the mechanism of hypermutation of immunoglobulin genes. We have studied individual clonal responses within germinal centres of spleen and Peyer's patches in young and old patient groups. Our results indicate that there is no difference in the actual mechanism of hypermutation with age. There are, however, differences that are due either to a change in selection processes or to a change in the founder cells available for activation.